The Interplay of Promptness and Effectiveness in Learning Recovery Programs: A Pathway to Post-Pandemic Educational Stability - Dixit, Rashi (Digital Repository of Theses, 2025)
The COVID-19 pandemic disrupted global education, impacting over 1.2 billion students. This study examines the effectiveness of Learning Recovery and Continuity Programs (LRCPs) in private primary schools, focusing on the impact of prompt implementation. Using a mixed-methods approach, data from school leaders revealed that early LRCP adoption significantly improved student engagement, attendance, and academic performance (rho = 0.604, p < 0.05). Key success factors included proactive leadership, robust technology, teacher training, and parental involvement, while barriers like insufficient infrastructure and training hindered progress. This research underscores the need for integrating LRCPs into educational policies, emphasizing crisis management training, international collaboration, and stronger digital infrastructure. The findings highlight actionable strategies to mitigate learning loss and build resilient education systems for future disruptions.